REGIONAL SYSTEMS OF HIGHER EDUCATION IN THE RUSSIAN FEDERATION: RESULTS OF REFORMING AND ADMINISTRATION EFFICIENCY - Vera I. Bazhenova; Anastasiya Ye. Sudakova; Inessa A. Gurban (Вестник Российского экономического университета имени Г. В. Плеханова, 2018)
The intensification of globalization processes and the creation of the international labour market have a considerable influence on the development of national tertiary education systems. The authors of the article have developed a methodology for diagnosing higher education systems at regional level. The following indicative parameters grouped into two blocks are used for such diagnostics: a) conditions of functioning and the state of higher education infrastructure; b) the state of educational and research activities in the higher education system. Based on the obtained results the authors come to a number of conclusions, with the most important implications related to the two trends in the higher education system in Russia: conservatism and development. The Russian higher education system conservatism manifests itself in the research component, academic staff and students’ scientific activity. Regions with strong tertiary research and education institutions are less affected by the state financial policy, therefore, the diagnostics results do not reveal a direct correlation between the level of research funding and the research outcomes. As regards the quantitative indicators of the infrastructure state (the specific quantity of capital assets), in this case we can talk about the development of the higher education system.